SILVER NANOPARTICLES-AQUEOUS LEAF EXTRACT OF SIDAGURI (SIDA RHOMBIFOLIA) AS REDUCING AGENTS (Jurnal Teknologi (Sciences & Engineering), 2024)
The Sidaguri leaf, scientifically known as Sida rhombifolia, is a plant species rich in flavonoids that have the ability to act as reducing agent in formation of silver nanoparticles. This study presented the synthesis of silver nanoparticles (AgNp-Sid) using aqueous leaf extract of sidaguri. This study utilized a concentration ratio of 2:90 mL aqueous leaf extract of Sidaguri and AgNO3 1 mM. The size and morphology of AgNp-Sid was measured using UV-Visible Spectrophotometer, PSA, FT-IR, SEM-EDS, and XRD. The investigation revealed an ordinary particle size of 63.5 nm with polydispersity index (PI) of 0.284. The maximum wavelength varies between 405.4 nm and 407.8 nm with the increasing of time. AgNp-Sid exhibited a spherical morphology and had a crystalline structure that is face-centered cubic. The results suggested that the aqueous leaf extract of sidaguri had the ability to function as a reducing agent in the synthesis of silver nanoparticles, offering a safe, cost-effective, and environmentally friendly alternative.